A theoretical study of noxious gases storage using covalent organic frameworks (COFs). (August 2020) - Xia, Liang; Yang, Yingjian; Chan, Yue
Abstract: Using covalent organic frameworks (COFs) to capture noxious gas has become an increasing research interest, especially for the purpose of environmental protection. A theoretical study on the interactions of carbon monoxide (CO), sulfur dioxide (SO2 ) and nitric oxide (NO), respectively with COF-300 has been proposed, based on the theory of the continuum approximation using Lennard-Jones potential. We discover that COF-300 can store more SO2 in comparison to CO and NO under an increasing pressure at 77K. The present methodology is computationally efficient and can be employed in other types of gases and nano-porous materials without conceptual difficulties.